2015
DOI: 10.1007/s00415-015-7779-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging evidence of gray and white matter damage and clinical correlates in progressive supranuclear palsy

Abstract: To evaluate gray matter (GM) and white matter (WM) abnormalities and their clinical correlates in patients with progressive supranuclear palsy (PSP). Sixteen PSP patients and sixteen age-matched healthy subjects underwent a clinical evaluation and multimodal magnetic resonance imaging, including three-dimensional T1-weighted imaging and diffusion tensor imaging (DTI). Volumetric and DTI analyses were computed using SPM and FSL tools. PSP patients showed GM volume decrease, involving the frontal cortex, putamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 48 publications
5
36
2
3
Order By: Relevance
“…Diffusion tensor imaging (DTI) allows for the assessment of directional water diffusion and the interrogation of specific white‐matter tracts. White‐matter tract degeneration has been demonstrated to be a striking feature of PSP‐RS, with abnormalities observed predominantly in the SCP, cerebellum, body of the corpus callosum, cingulum, white‐matter laminar of the thalamus, and premotor aspects of the superior longitudinal fasciculus . The majority of these white‐matter tracts show greater degeneration in PSP‐RS compared with PD and MSA‐P .…”
Section: Structural Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion tensor imaging (DTI) allows for the assessment of directional water diffusion and the interrogation of specific white‐matter tracts. White‐matter tract degeneration has been demonstrated to be a striking feature of PSP‐RS, with abnormalities observed predominantly in the SCP, cerebellum, body of the corpus callosum, cingulum, white‐matter laminar of the thalamus, and premotor aspects of the superior longitudinal fasciculus . The majority of these white‐matter tracts show greater degeneration in PSP‐RS compared with PD and MSA‐P .…”
Section: Structural Mrimentioning
confidence: 99%
“…White-matter tract degeneration has been demonstrated to be a striking feature of PSP-RS, with abnormalities observed predominantly in the SCP, cerebellum, body of the corpus callosum, cingulum, white-matter laminar of the thalamus, and premotor aspects of the superior longitudinal fasciculus. 63,[111][112][113][114][115][116][117][118][119][120][121][122][123][124] The majority of these white-matter tracts show greater degeneration in PSP-RS compared with PD 112,118,122,[125][126][127] and MSA-P. 72,118,126 Little data are currently available on the diagnostic utility of DTI measures, although the corpus callosum 113 and SCP 125 show high sensitivity and specificity in differentiating PSP-RS and PD. There is also evidence that adding DTI measures to the MRPI may help in the differentiation of PSP-RS from controls.…”
Section: Diffusion Imagingmentioning
confidence: 99%
“…MRI studies have revealed gray matter abnormalities at multiple brain levels in both PSP and CBS: subcortical nuclei pathology is involved in both conditions, but PSP patients exhibit predominant midbrain atrophy and a limited involvement of frontal cortex pathology, while CBS patients display more evident cortical atrophy, particularly in peri-rolandic areas (47). Moreover, diffusion tensor imaging has revealed widespread white matter bundle damage, which suggests altered structural connectivity between cortical and subcortical structures, in both PSP and CBS patients (48).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diffusion tensor imaging has revealed widespread white matter bundle damage, which suggests altered structural connectivity between cortical and subcortical structures, in both PSP and CBS patients (48). …”
Section: Introductionmentioning
confidence: 99%
“…DTI is a valuable noninvasive imaging technique for the assessment of the WM structure of the brain. In patients with PSP-RS, relative to PD patients and healthy controls, a greater WM degeneration (lower FA and higher MD) have been observed in the superior cerebellar peduncles, cerebellum, corpus callosum, cingulum, superior longitudinal fasciculus, and white matter laminar of thalamus (Blain et al, 2006;Canu et al, 2011;Erbetta et al, 2009;Ito, Makino, Shirai, & Hattori, 2008;Knake et al, 2010;Piattella et al, 2015;Saini et al, 2012;Surova et al, 2015). In patients with PSP-RS, relative to PD patients and healthy controls, a greater WM degeneration (lower FA and higher MD) have been observed in the superior cerebellar peduncles, cerebellum, corpus callosum, cingulum, superior longitudinal fasciculus, and white matter laminar of thalamus (Blain et al, 2006;Canu et al, 2011;Erbetta et al, 2009;Ito, Makino, Shirai, & Hattori, 2008;Knake et al, 2010;Piattella et al, 2015;Saini et al, 2012;Surova et al, 2015).…”
mentioning
confidence: 99%